PELATIHAN BAHASA INGGRIS MELALUI PEMBUATAN KERAJINAN TANGAN DARI SAMPAH NON ORGANIK PADA SISWA SD - elinofriati, Eli Nofriati; Listia Dewi, Silvi; Misnar, Misnar; Misnawati, Misnawati; Zuraini, Zuraini (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
The title of this Service Community Activity is the Training of English through the activity of making handy crafts from nonorganic wastes in elementary school students. The activity was done by given the training to the students to learn English vocabulary through the making of handy crafts from nonorganic wastes such as flower arrangement. The purpose of the training is to help the students in learning various English vocabularies. Through this training the students are expected to be able to mention and remember the English vocabulary related to the activity. For example, the students can pronounce the words such as: flower petals (kelopak bunga), leaves (daun), flower pistil (putik bunga), stalk (tangkai), cut out (menggunting), stringing (merangkai) and etc. This activity was held for one month starting from doing observation, preparing of the proposal, doing the training and ended by preparing the report. The activity and the training was held on January 2022 of the second week. During the training, the students were taught about the English vocabulary while aranging the flowers from the nonorganic waste. After doing the training, the result that can be found that the students were able to mention and pronounce the English vocabulary well and the students also could make and create the handy craft (flowers) from the nonorganic waste. Based on the result of the service community activity to the students of SDN 3 Muara Batu can be concluded that the training was done successfully.